ANALISIS PENERAPAN PERHITUNGAN DAN PELAPORAN PAJAK PENGHASILAN PASAL 23 DAN PPH 25 PADA PT. CITRA BUANA INDOLOKA - Muhammad Rizky Alif (2020)
This study aims to determine the amount of Article 23 Income Tax and Article 25 Income Tax deposited and to determine whether the calculation and reporting of Article 23 of Income Tax and Article 25 of Income Tax at PT. Citra Buana Indoloka is in accordance with the Law on Income Taxes. The object of research was taken at PT. Citra Buana Indoloka. The method used in this research is qualitative with interpretive paradigm and ethnometodical approach. From the results of the study it can be concluded that Article 23 Income Tax affects the amount of Article 25 income tax installments and is in accordance with existing rules, it's just that the reporting of Income Tax 25 is not timely.